Moremi The Courageous Queen - Ajayi, Segun Thomas (Rasmed Publications Ltd, 2007)
Queen Moremi lived in Ile Ife, She decided to liberate her people from the gruesome hands of the arch enemies of the Ifes.
Keywords: Plays